Procedure for Handling 4-H Accounts: Tax-Related Procedures for 4-H Clubs and Affiliated Groups - Marilyn Norman; Joy C. Jordan (EDIS, 2009)
Revised! 4H5.7, a 3-page factsheet by Marilyn N. Norman and Joy C. Jordan, details correct tax procedures for 4-H clubs. Includes information on exemptions, receiving donations, state tax, and getting on the IRS list of charitable organizations. Includes references. Published by the Florida 4-H Program, October 2009.